PENGARUH PENGGUNAAN INTERNET TERHADAP LITERASI KELUARGA - Tarma; Maya Oktaviani (Perspektif Ilmu Pendidikan, 2019)
This research aims to determine the effect of internet usage on family literacy. The study was conducted with a survey method of 100 families in the area of Candi Batujaya, Karawang. A non-test instrument in the form of a family literacy questionnaire consisting of 50 items with a verbal frequency scale (4 scales) of always, often, rarely, and never was used. Data were analyzed using the t-test. Before analyzing the data, normality and homogeneity tests were performed to meet normal and homogeneous assumptions. The results showed that internet usage inﬂuenced family literacy even though relatively small (6.15%). Collaborative monitoring was the highest means score (2.89 out of 4.00), while parent involvement was the lowest means score (2.40 out of 4.00).